2020
DOI: 10.1021/acs.orglett.0c01747
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal-Activation Strategy for Allylic Sulfination with Unactivated Allylic Alcohols

Abstract: A reciprocal-activation strategy for allylic sulfination with unactivated allylic alcohols was developed. In this reaction, the hydrogen bond interaction between allylic alcohols and sulfinic acids allowed for reciprocal activation, which enabled a dehydrative cross-coupling process to occur under mild reaction conditions. This reaction worked in an environmentally friendly manner, yielding water as the only byproduct. A variety of allylic sulfones could be obtained in good to excellent yields with wide functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…It has previously been shown that Ca(NTf 2 ) 2 and PF 6 salts underwent anion metathesis to form KNTf 2 and Ca(NTf 2 )PF 6 . 20 The latter salt, more Lewis acidic than Ca(NTf 2 ) 2 and displaying two binding sites available on the calcium center, was reported to activate a wide range of substrates such as cyclopropanes, [39][40] carbonyl compounds, [41][42] alcohols, [43][44][45][46][47][48] alkenes 49,50 or more recently sulfonyl 51,52 fluorides. 20,28,53 Ca(NTf 2 )PF 6 , whose Lewis acidity has been evaluated by the Childs method, 41 has also been associated with hexafluoroisopropanol as the solvent and the resulting system shown by Gandon and Leboeuf to be highly active in various transformations including Aza-Piancatelli, 54,55 hydroarylation, 56 or hydroamidation 57 or hydroacyloxylation 58 reactions.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that Ca(NTf 2 ) 2 and PF 6 salts underwent anion metathesis to form KNTf 2 and Ca(NTf 2 )PF 6 . 20 The latter salt, more Lewis acidic than Ca(NTf 2 ) 2 and displaying two binding sites available on the calcium center, was reported to activate a wide range of substrates such as cyclopropanes, [39][40] carbonyl compounds, [41][42] alcohols, [43][44][45][46][47][48] alkenes 49,50 or more recently sulfonyl 51,52 fluorides. 20,28,53 Ca(NTf 2 )PF 6 , whose Lewis acidity has been evaluated by the Childs method, 41 has also been associated with hexafluoroisopropanol as the solvent and the resulting system shown by Gandon and Leboeuf to be highly active in various transformations including Aza-Piancatelli, 54,55 hydroarylation, 56 or hydroamidation 57 or hydroacyloxylation 58 reactions.…”
Section: Resultsmentioning
confidence: 99%
“…To the best knowledge, such a mild and activator‐free synthesis of allylic sulfones from non‐derivatized allylic alcohols has not been reported yet. [ 16 ] Interestingly, an obvious promoting effect of water was observed, and rather than the using of precious ligands in activator‐free Tsuji–Trost reactions in aqueous media, [ 17 ] only the simple and easily‐available Pd(PPh 3 ) 4 is used by this new method. Detailed mechanism studies by various NMR techniques and theoretical calculations suggested that the sulfinic acid‐assisted activation of allylic alcohol through a six‐membered ring species may be not the main path, and a novel water‐mediated and substrate self‐assisted activation of allylic alcohols through an eight‐membered ring species via hydrogen bonding may be involved in the aqueous reactions (Scheme 1D).…”
Section: Methodsmentioning
confidence: 99%
“…Due to its poor leaving ability, the hydroxyl group usually needs to be activated by a Lewis acid or a Brönsted acid (Scheme , eq 1). , A Ph 3 P/NBS system can also effectively activate the hydroxyl group for arylsulfonylation (eq 2) . The Pd-catalyzed allylic substitution with the activation of the hydroxyl group has served as an efficient approach for the dehydroxylative sulfonylation (eq 3) . Shen’s reagent [N-SCF 3 ], which has proved to be a good trifluoromethylthiolation reagent, can also act as a CF 3 S source for sulfonylation of allylic and propargyl alcohols (eq 4, right side) .…”
mentioning
confidence: 99%